Sanksi Pidana terhadap Oknum Guru Olahraga yang Melakukan Kekerasan Seksual Kepada Anak Didiknya (Putusan Nomor 325/PID.SUS/2020/PN DPS) - A.A.SG. Istri Sinta Maharani; A.A. Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
Sexual violence is carried out regardless of social status, such as cases of sexual violence perpetrated by teachers against their students. With the decision issued by the Denpasar District Court No. 325/Pid.Sus/2020/PN Dps. A case of sexual violence that has occurred in an elementary school in Sembung Village, Mengwi, Badung. The purpose of this research is to analyze the criminal penalties for individual educators who commit acts of sexual violence against their students and discuss the judge's considerations in imposing criminal sanctions on educators who have acted immorally on their students according to decision Number 325/Pid.Sus/ 2020/PN Dps. In this case the researcher uses normative law as a research method, using a statutory approach and a conceptual approach. The sources of legal materials for this research are primary materials and secondary materials. Data collection techniques using note-taking techniques, and documentation techniques. The results of the research explained that the regulation of sexual violence that has been regulated in Book II Chapter XIV of the Criminal Code concerning Crimes Against Morals, and the Judge in determining the appropriate punishment for the defendant, must pay attention and arrange considerations so that the judge in making a decision, and the reasons clear and detailed.